A hybrid case based reasoning system using fuzzy-rough sets and formal concept analysis - Tadrat, Jirapond; Boonjing, Veera; Pattaraintakorn, Puntip (My University, 2007)
In this paper, we propose a new hybrid case based reasoning system based on rough set theory, formal concept analysis and fuzzy sets. This system applies rough set theory to assure minimally sufficient cases in its case base. It uses formal concept analysis to reveal knowledge of attribute dependencies in terms of concept lattices. Numeric attributes are transformed to be suitable for formal concept analysis using fuzzy sets. © 2007 IEEE.